ANTESEDEN BEHAVIORAL INTENTIONS PADA PENGGUNA JASA TRANSPORTASI BUS TARIF PREMIUM - Yasintha Soelasih; Reinandus Aditya Gunawan (Jurnal Manajemen dan Pemasaran Jasa, 2019)
The purpose of this study is to examine service quality, location, and personal characteristic toward behavioral intentions of premium bus fare transportation. Therefore, this research emphasizes consumer behavior in the use of public transportation, especially premium ones. This study uses 217 data, which aredone by validity and reliability tests, and the hyphotheses are analyzed by usingstructural equation modeling (SEM). The results showed that service quality and location have an influence on behavioral intentions, while personal characteristics do not have an influence on behavioral intentions. The implication of this research is to pay attention to premium bus transportation providers in the selection of locations.